Robin Collyer : paysages - Grout, Catherine (CV Photo)

(untitled) (Les Productions Ciel variable, 2001)
A series of ten photographs made by Robin Collyer subtly responds to a private commission in memory of someone who has died. These views show various New Brunswick landscapes that recall both archetypes and a daily reality that is more or less common to those who live in the region. The views of a potato field and the façade of an office evoke the place where a specific family lives, whose story is attached to the site. View could be the portrait of someone contemplating the landscape, perpetuating the association between it and the gaze, between the landscape represented and the landscape shaped by human beings.